2013
DOI: 10.2106/jbjs.k.00756
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Decrease Postoperative Infections Following Posterior Cervical Spine Surgery

Abstract: In this study, preliminary preparation with alcohol foam and the placement of suprafascial drains for deep wounds resulted in one postoperative deep infection in 323 surgical procedures. The addition of intrawound vancomycin powder in 195 consecutive posterior cervical spine surgical procedures resulted in no infections and no adverse effects. To our knowledge, this is the first description of a technique for significantly decreasing postoperative cervical spine infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
98
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 15 publications
4
98
1
2
Order By: Relevance
“…Cohort studies showed that vancomycin powder significantly reduced postoperative SSIs in adult thoracolumbar fusion surgery (n = 165-1732, 2.6%-12% vs 0%-0.2%, p < 0.001), 21,22 posterior fusion after traumatic etiologies (n = 110, 13% vs 0%, p = 0.02), 15 and posterior cervical decompression and fusion surgeries (n = 171-576, 1.73%-15% vs 0%-2.5%, p < 0.05). 2,17,20 Similarly, after introduction of vancomycin powder, Molinari et al reported a low (1.20%) SSI rate in spine fusion surgery (n = 663), 14 and Gans et al reported a low (3.4%) SSI rate in pediatric spine deformity fusion cas- es (n = 87). 3 In a cost analysis, Godil et al postulated that decreased SSI rates due to vancomycin powder can lead to a potential cost savings of $438,165 per 100 patients.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Cohort studies showed that vancomycin powder significantly reduced postoperative SSIs in adult thoracolumbar fusion surgery (n = 165-1732, 2.6%-12% vs 0%-0.2%, p < 0.001), 21,22 posterior fusion after traumatic etiologies (n = 110, 13% vs 0%, p = 0.02), 15 and posterior cervical decompression and fusion surgeries (n = 171-576, 1.73%-15% vs 0%-2.5%, p < 0.05). 2,17,20 Similarly, after introduction of vancomycin powder, Molinari et al reported a low (1.20%) SSI rate in spine fusion surgery (n = 663), 14 and Gans et al reported a low (3.4%) SSI rate in pediatric spine deformity fusion cas- es (n = 87). 3 In a cost analysis, Godil et al postulated that decreased SSI rates due to vancomycin powder can lead to a potential cost savings of $438,165 per 100 patients.…”
Section: Discussionmentioning
confidence: 98%
“…Most initial studies have supported adjunctive powdered vancomycin, reporting decreased rates of postoperative wound infection and no adverse side effects. 2,3,14,15,17,[20][21][22]24 Local vancomycin has long been tested in sternotomy wounds following cardiac surgery. In a 1989 blinded, randomized study involving 416 patients, Vander Salm et al reported a significant reduction of sternal infections (3.6% vs 0.45%, p = 0.02) with topical vancomycin applied to the cut edges of the sternum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations